2010
DOI: 10.4088/jcp.08m04411gry
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports of Postmarketing Adverse Event Experiences With Olanzapine Intramuscular Treatment in Patients With Agitation

Abstract: Clinicians should use care when treating agitated patients, especially when they present with concurrent medical conditions and are treated with multiple medications, which may increase the risk of poor or even fatal outcomes. Clinicians should use caution when using olanzapine IM and parenteral benzodiazepines simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…Respiratory depression was more frequent with olanzapine and quetiapine. In a study of fatalities documented in postmarketing safety reports, Marder et al (43) found the frequency of respiratory effects was second only to cardiovascular effects for olanzapine. Two other reports found quetiapine to be associated with respiratory depression in severe cases (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory depression was more frequent with olanzapine and quetiapine. In a study of fatalities documented in postmarketing safety reports, Marder et al (43) found the frequency of respiratory effects was second only to cardiovascular effects for olanzapine. Two other reports found quetiapine to be associated with respiratory depression in severe cases (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…A critical risk may be represented by elderly, potentially at risk of altered level of consciousness and falls [132].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Rationale for combining an anticholinergic or benzodiazepine with the antipsychotic agent may be to mitigate potential extrapyramidal side effects, added calming effect, or to intensify the level of sedation 4,11,12. Despite an absence of strong evidence supporting the safe use of parenteral olanzapine-benzodiazepine combination, it is used in psychiatric emergency departments 13-16…”
Section: Introductionmentioning
confidence: 99%